Sectoral Futures Are Conditional on Choices of Global and National Scenarios – Australian Marine Examples - Boschetti, Fabio; Bulman, Catherine M.; Hobday, Alistair J.; Fulton, Elizabeth A.; Contardo, Stephanie; Lozano-Montes, Hector; Robinson, Lucy M.; Smith, Anthony D. M.; Strzelecki, Joanna; Ingrid van Putten, E. (Frontiers in Marine Science, 2020)
Planning and management require expectations of future system behaviour. These expectations can come in the form of predictions, projections, scenarios, narratives, visions and intuitions, at different spatial and temporal scales. While each can provide different insights into a system future, it is not clear how they can be effectively combined into a unified analysis. Here, we propose a general framework to combine conceptual models, numerical projections and scenario narratives, leading to a system view of the functioning of the future Blue Economy sectors as applied to Australian oceans. We start by developing a conceptual model of the sectors directly or indirectly interacting with the Australian oceans and their national and global drivers. We then identify scenarios and projections for each global driver as well as projections of future development for the national drivers and for the Blue Economy sectors. Comparisons of the global scenarios, national projections and sectoral projections suggest that the Australian marine sectors expect to follow a path of growth mostly driven by market forces enabled by government regulations. The analysis of each sector provides information on the extent to which the initial conceptual model can be improved as part of more detailed analysis at a sectoral level. This approach supports sector-based marine planning with a consistent and repeatable framing and can help researchers, managers and stakeholders reach a shared understanding of system interactions and the potential impact of future shocks to national and international drivers